1996
DOI: 10.1007/bf00013730
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data on rotifers in the interstitial of the Ninnescah river, Kansas, USA

Abstract: One-hundred five rotifer species were identified from a sandy, plains river in Kansas, USA (the Ninnescah river) . Of those rotifers identified, eighty occurred only in the interstitial sand, fifty-six in only the flow as plankton, and thirty-one from both habitats . Most species can be characterized as being more commonly found in littoral habitats, and not the interstitial or plankton . Lecane inermis (Bryce, 1892) had the highest density in the hygropsammon interstitial with an average 401 ind . 10 cm -3 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The diversity of psammon rotifers in Bau Thiem Lake (89 taxa observed, Chao2 = 99, Jack2 = 115 taxa estimated) is lower than the 119 taxa (130 samples) observed from Mikolajskie Lake, north-eastern Poland (Muirhead et al, 2006), and the 105 species identified from interstitial sand of Ninnescah river, USA (Turner, 1996). On the other hand, it is much higher than the 19 taxa (2 samples) observed from Mai Khao peat swamp on Phuket Island, Thailand (Segers & Chittapun, 2001), 24 taxa (5 samples) in Jelén Lake, 26 taxa (5 samples) in Rekowskie Lake and 10 taxa (5 samples) in Pomysko Lake, Poland (Bielańska-Grajner, 2001), and 48 taxa in Piaseczno Lake, Poland (Radwan & Bielańska-Grajner, 2001).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The diversity of psammon rotifers in Bau Thiem Lake (89 taxa observed, Chao2 = 99, Jack2 = 115 taxa estimated) is lower than the 119 taxa (130 samples) observed from Mikolajskie Lake, north-eastern Poland (Muirhead et al, 2006), and the 105 species identified from interstitial sand of Ninnescah river, USA (Turner, 1996). On the other hand, it is much higher than the 19 taxa (2 samples) observed from Mai Khao peat swamp on Phuket Island, Thailand (Segers & Chittapun, 2001), 24 taxa (5 samples) in Jelén Lake, 26 taxa (5 samples) in Rekowskie Lake and 10 taxa (5 samples) in Pomysko Lake, Poland (Bielańska-Grajner, 2001), and 48 taxa in Piaseczno Lake, Poland (Radwan & Bielańska-Grajner, 2001).…”
Section: Discussionmentioning
confidence: 70%
“…Accordingly, he characterised the organisms inhabiting the psammon as psammobiontic, those organisms that live exclusively, except fortuitously, in the psammon; psammophile, those that show a clear preference for the psammon, but which may also be found in the littoral; and psammoxene, those that avoid the psammon (Wiszniewski, 1937). Notwithstanding that there is a substantial body of recent literature on psammon and interstitial habitats in lotic (Schmid-Araya, 1995, 1998Turner, 1996) as well as in lentic freshwater environments (Wiszniewski, 1934a(Wiszniewski, , 1934bMyers, 1936;Pennak, 1939;Bielańska-Grajner, 2001Radwan & Bielańska-Grajner, 2001;Ejsmont-Karabin, 2004), there are particularly few studies on these habitats in (sub)tropical regions. Recently, Segers and Chittapun (2001) reported on a limited collection of interstitial rotifers from a peat swamp on Phuket Island, Thailand, and described three new rotifer species, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have also been published on the sand and interstitial rotifers of rivers and streams (Zullini & Ricci, 1980;Pennak & Ward, 1986;Schmid-Araya, 1994, 1995Turner, 1996;Turner & Distler, 1995). There is less information on psammic rotifers living in stagnant waters (Wiszniewski, 1932(Wiszniewski, , 1934a1947;Neel, 1948;Segers, 1998;Ejsmont-Karabin, 2003;Bielan´ska-Grajner, 2001;Radwan & Bielan´ska-Grajner, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…Lecane hastata is described in the literature as a cosmopolitan species that can be found in the periphyton and psammon of both brackish and freshwater habitats (Koste 1978;Segers 1995;Turner 1996).…”
Section: Rhinoglena Frontalis Ehrenberg 1853mentioning
confidence: 99%
“…Wulfert, 1939 (Figs 1I and 2H) Sporadic individuals of E. wiszniewskii were found in samples collected at Viadana throughout the summer and autumn 2009. It is reported in the literature as a typical inhabitant of the river psammon (Turner 1996;De Smet & Pourriot 1997).…”
Section: Resticula Ancepsmentioning
confidence: 99%